2008
DOI: 10.1109/tac.2008.923738
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Complementary Filters on the Special Orthogonal Group

Abstract: 16International audienceThis paper considers the problem of obtaining good attitude estimates from measurements obtained from typical low cost inertial measurement units. The outputs of such systems are characterized by high noise levels and time varying additive biases. We formulate the filtering problem as deterministic observer kinematics posed directly on the special orthogonal group SO(3) driven by reconstructed attitude and angular velocity measurements. Lyapunov analysis results for the proposed observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
1,299
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,485 publications
(1,313 citation statements)
references
References 37 publications
(63 reference statements)
6
1,299
0
8
Order By: Relevance
“…This is important since f n = −g n due to wave excitation of the vessel. The attitude observer, Σ 1 , by Grip et al [22], developed from [23], is given as…”
Section: Estimating the Total Vessel Motion And The Gyro Biasmentioning
confidence: 99%
“…This is important since f n = −g n due to wave excitation of the vessel. The attitude observer, Σ 1 , by Grip et al [22], developed from [23], is given as…”
Section: Estimating the Total Vessel Motion And The Gyro Biasmentioning
confidence: 99%
“…Hua [16] used the vector-based attitude observer of Hamel and Mahony [17] and Mahony, Hamel, and Pflimlin [8] as the basis for an attitude and velocity observer that depends only on inertial measurements, GNSS velocity measurements, and magnetometer measurements. Hua's observer exploits the fact that the vehicle's acceleration vector in the navigation frame is implicitly available in the derivative of the GNSS velocity.…”
Section: A Nonlinear Observers For Gnss/ins Integrationmentioning
confidence: 99%
“…For this purpose we use the Complementary filter (CF) [13], which integrates the gyroscopic measurements ω and corrects them with measurements of known directions v i . The state of the filter consists of the attitude represented by a unit quaternionq and a vector of additive gyroscope biasesb g .…”
Section: Attitude Estimation With the Complementary Filtermentioning
confidence: 99%
“…To overcome this problem, EKFs using the Inertia Measurement Unit (IMU) directly in the prediction step were proposed [12]. Focussing only on the attitude estimation based on an IMU, Mahony et al [13] introduced the concept of the Complementary filter (CF) and demonstrated its performance on a micro aerial vehicle. This variety of solutions require a deeper investigation on how the IMU should be used in an EKF.…”
Section: Introductionmentioning
confidence: 99%